GRAFFITI BERBAHASA MINANGKABAU PADA ANGKUTAN KOTA DI KOTA PADANG - Zilda Alamanda (Jurnal Elektronik WACANA ETNIK, 2010)
This article describes lingual forms, function, and meaning of graffiti on mass transportation in Padang. On this research, data was obtained from interview with the drivers and co drivers. The result shows there are three lingual forms (word, phrase, and sentence), seven functions (instrumental, regulatory, representational, interactional, personal, heuristic, and imaginative), and three meaning (lexical, grammatical, and contextual) on the objects.